Flexible polarization configuration in high-entropy piezoelectrics with high performance. (1st September 2022) - Liu, Ye; Yang, Jiyuan; Deng, Shiqing; Zhang, Yueyun; Zhang, Yongcheng; Sun, Shengdong; Wang, Lu; Jiang, Xiaodong; Huo, Chuanrui; Liu, Hui; Qi, He; Liu, Shi; et al.
Abstract: Polarization configuration engineering by compositional and structural tuning in piezoelectrics holds great promise for high piezoelectricity that benefits wide electromechanical applications. Here, a novel flexible polarization configuration is achieved in high-entropy Pb-based perovskites, which contributes to superior piezoelectricity of d 33 ∼1200 pC/N. Emergent characteristics and behaviors of such a flexible polarization configuration are thoroughly investigated by the combination of atomic-scale scanning transmission electron microscopy, in-situ high-energy synchrotron X-ray diffraction, and first-principles calculations. The multiple interactions among the A and B -site atoms, originating from the increase of the species of B -site elements as well as the enhanced entropy of the system, weaken the long-range polarization order, enhance the flexibility of the polarization under the external field, and eventually result in the high piezoelectric performance. This work demonstrates that polarization configuration engineering through the high-entropy method would be an effective strategy for obtaining outstanding piezoelectric properties, which provides new opportunities for the design and discovery of high-performance piezoelectrics. Graphical abstract: Image, graphical abstract